Efficacy of ranibizumab combined with photodynamic therapy on wet age-related macular degeneration - Chen, Ling (Exp Ther Med, 2020)
Efficacy and safety of intravitreal ranibizumab (IVR) combined with photodynamic therapy (PDT) in treating wet age-related macular degeneration (wAMD) were studied. A total of 130 eyes were collected from 130 wAMD patients treated in Affiliated to Qingdao University Yuhuangding Hospital of Yantai, of which 65 were given IVR combined with PDT (combination therapy group) and the remaining 65 were treated with simple IVR (ranibizumab group). The differences in best corrected visual acuity (BCVA), central macular thickness (CMT), intraocular pressure, choroidal neovascularization (CNV) leakage, levels of serum vascular endothelial growth factor (VEGF) and transforming growth factor-β1 (TGF-β1) as well as complication rate were compared before and after treatment between the two groups. At 1, 3, 6 and 12 months after treatment, combination therapy group had remarkably better BCVA and notably smaller CMT than ranibizumab group. Fundus fluorescein angiography (FFA) showed that the area of macular degeneration was reduced markedly after treatment in both groups, and the area in combination therapy group was evidently smaller than that in ranibizumab group at 1, 3 and 6 months after treatment. At 3 months after treatment, the levels of serum VEGF and TGF-β1 declined obviously in the two groups compared with those before treatment. The IVR combined with PDT can effectively improve the visual acuity, decrease CMT and prominently reduce the area of macular degeneration of wAMD patients, and its therapeutic effects are long-standing and tolerable for the patients, so it is worthy of clinical popularization.